2014
DOI: 10.1002/2014jc010227
|View full text |Cite
|
Sign up to set email alerts
|

Air‐sea exchange of methanol and acetone during HiWinGS: Estimation of air phase, water phase gas transfer velocities

Abstract: The air-sea fluxes of methanol and acetone were measured concurrently using a protontransfer-reaction mass spectrometer (PTR-MS) with the eddy covariance (EC) technique during the High Wind Gas Exchange Study (HiWinGS) in 2013. The seawater concentrations of these compounds were also measured twice daily with the same PTR-MS coupled to a membrane inlet. Dissolved concentrations near the surface ranged from 7 to 28 nM for methanol and from 3 to 9 nM for acetone. Both gases were consistently transported from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
56
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 77 publications
13
56
1
Order By: Relevance
“…Recent direct flux measurements of methanol also demonstrated a consistent flux of methanol from the atmosphere to surface waters along a meridional transect of the remote Atlantic Ocean (Yang 15 et al 2013) and the Greenland Sea (Yang et al 2014b). Methanol is ubiquitous in atmospheric and marine environments where seawater concentrations have been reported ranging between <27 and 429 nM (Williams et al 2004, Kameyama et al 2010, Yang et al 2013, Yang et al 2014b, Beale et al 2015). An annual study in the western English Channel reported surface seawater methanol concentrations ranging between 16 and 20 78 nM over an annual cycle with no obvious seasonality (Beale et al 2015).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recent direct flux measurements of methanol also demonstrated a consistent flux of methanol from the atmosphere to surface waters along a meridional transect of the remote Atlantic Ocean (Yang 15 et al 2013) and the Greenland Sea (Yang et al 2014b). Methanol is ubiquitous in atmospheric and marine environments where seawater concentrations have been reported ranging between <27 and 429 nM (Williams et al 2004, Kameyama et al 2010, Yang et al 2013, Yang et al 2014b, Beale et al 2015). An annual study in the western English Channel reported surface seawater methanol concentrations ranging between 16 and 20 78 nM over an annual cycle with no obvious seasonality (Beale et al 2015).…”
Section: Introductionmentioning
confidence: 92%
“…A net air-to-sea flux was first demonstrated in Northern temperate waters by Beale et al (2013). Recent direct flux measurements of methanol also demonstrated a consistent flux of methanol from the atmosphere to surface waters along a meridional transect of the remote Atlantic Ocean (Yang 15 et al 2013) and the Greenland Sea (Yang et al 2014b). Methanol is ubiquitous in atmospheric and marine environments where seawater concentrations have been reported ranging between <27 and 429 nM (Williams et al 2004, Kameyama et al 2010, Yang et al 2013, Yang et al 2014b, Beale et al 2015).…”
Section: Introductionmentioning
confidence: 97%
“…We calculate attitude and velocity following the complimentary filtering approach of Edson et al (1998); this method is routinely used to motioncorrect ship-borne turbulence measurements (e.g. McGillis et al, 2001;Brooks, 2008;Norris et al, 2012;Yang et al, 2014;Drennan et al, 2014;Landwehr et al, 2015;Prytherch et al, 2015). The ship's mean horizontal velocity when underway can approach 6 m s −1 ; the wave-induced velocity per- Because the lidar Doppler velocities are 2 s averages, we use a corresponding 2 s averaged platform velocity to correct them; the standard deviation of the individual 10 Hz platform velocity measurements is also calculated as a quality control measure, in order to flag measurements for which the ship motion changes substantially during the lidar measurement interval and to provide a measure of the noise added to the Doppler winds by the ship motion.…”
Section: Ship-motion Stabilisationmentioning
confidence: 99%
“…This version of COARE removes the reliance on earlier ship measurements of COARE3.0 (Fairall et al, 2003) which may be subject to air-flow distortion effects, and provides better 25 agreement with independent observations (e.g. Yang et al, 2014). COARE3.5 was also used to compute u*, U10n (U10 adjusted to neutral stability), bulk sensible and latent heat fluxes.…”
Section: Environmental Measurementsmentioning
confidence: 99%